2021
DOI: 10.24200/amecj.v4.i02.144
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid functionlized on multiwall carbon nanotubes for nickel and lead determination in human serum and urine samples by micro solid-phase extraction

Abstract: In this study, a novel synthesis adsorbent, 1-(3-aminopropyl)-3-methylimidazolium hexafluorophosphate functionlized on multiwall carbon nanotubes ([Apmim][PF6]-MWCNTs, IL@MWCNTS) was used for nickel/lead (Ni/Pb) extraction and determination by dispersive ionic liquid micro solid-phase extraction (DIL-μ-SPE) coupled to electrothermal atomic absorption spectrometry (ET-AAS). After dilution of 20 mg of IL@MWCNTS in 200 μL of acetone, the mixture was injected to 10 mL of human serum/urine samples at pH of 8.0. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…GreET usage also reduces the risk of analyte degradation and matrix changes due to enzymatic conversion, as well as fast sample collection and clean-up. Different examples of applications involving blood sampling using GreETs can be found in the literature, such as VOCs (SPME [77]), polycyclic aromatic hydrocarbons (PAHs, pipette-tip SPE [78]), Ni and Pb (µSPE [79]), opiates (MEPS [70]), and antidepressants (FPSE [80]). SPME has also been reported in in vivo assays with biological matrices like tissues.…”
Section: Biological Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…GreET usage also reduces the risk of analyte degradation and matrix changes due to enzymatic conversion, as well as fast sample collection and clean-up. Different examples of applications involving blood sampling using GreETs can be found in the literature, such as VOCs (SPME [77]), polycyclic aromatic hydrocarbons (PAHs, pipette-tip SPE [78]), Ni and Pb (µSPE [79]), opiates (MEPS [70]), and antidepressants (FPSE [80]). SPME has also been reported in in vivo assays with biological matrices like tissues.…”
Section: Biological Samplesmentioning
confidence: 99%
“…MSPE allowed the extraction of trace metals in food products [127] (additional examples available in Table S2). Moreover, studies have shown that this technique can be used for the determination of acrylamide [78,79], bisphenols [80], PAHs [128], plant growth regulators [129], and caffeine [130]. FPSE is another GreET that has been shown to be very useful for the determination of several classes of pesticides in foods [96].…”
Section: Food Samplesmentioning
confidence: 99%
“…4,5 It is not easy to trace heavy metals in low quantities. The current advanced analytical methods such as atomic uorescence spectroscopy (AFS), inductive coupled plasma mass spectroscopy (ICP-MS), and atomic absorption spectroscopy (AAS) [7][8][9][10][11] have shown satisfactory results. However, those methods are fraught with difficulties, including multi-step, time-consuming, and expensive procedures.…”
Section: Introductionmentioning
confidence: 99%